Application of the Mudharabah Agreement in the Profit Sharing System for Raising Cattle (Study in Penago II Village, Ilir Talo District, Seluma Regency) - Nur Wahidah, Titi; Asnaini, Asnaini; Makmur, Makmur (Sharia Economic and Management Business Journal (SEMBJ), 2024)
The purpose of this research is to find out how the application of the contract that has been running in Penago II Village, Ilir Talo Subdistrict, Seluma Regency and to find out the application of the mudharabah contract on the profit sharing of raising cattle in Penago II Village, Ilir Talo Subdistrict, Seluma Regency. This research uses a qualitative descriptive approach. Informants in the study were 8 people. Data collection techniques using observation, interviews, and documentation. Data analysis techniques use data reduction, data presentation and conclusion drawing. From the results of the research and discussion, it is concluded that the application of the contract that occurred in Penago II Village uses agreements and profit sharing, capital, profit sharing, risks and continuation of the contract if one of the parties dies, influencing factors, various types of cows that are in the field, and the time period. the agreement is only done verbally only trust each other in making this agreement, the profit sharing system in the mudharabah contract carried out between the owner and the manager in Penago II Village. With the division of the ratio divided 60:40. This occurs by agreement between the two parties. If in the process of this contract there is a loss, it will be borne by both parties, as long as the mistake is not due to the negligence of the manager. The profit sharing carried out by the people of Penago II Village is in accordance with the concept of mudharabah in Islamic Economics, namely, capital, management, collateral, time period and profit ratio to the manager. So that the profit sharing carried out by the people of Penago II Village is going well.